The Wordsworth Dictionary of Musical Quotations - Watson, Derek (Wordsworth Editions Ltd, 1994)
This is a comprehensive and entertaining collection of musical insights, incorporating critical remarks and waggish definitions, biographical sketches and laconic bons mots.
Keywords: Dictionary-Music-Quotations-Reference